Upper Ordovician sponge spicules from Gondwana: New data from Peru and Libya - Gutiérrez Marco, Juan Carlos (2016)
Trabajo presentado en Simposio ICGP 591 ‘The Early to Middle Palaeozoic Revolution’, Closing Meeting Abstract, Ghent University, Belgium, 6-9 july 2016.